PENGARUH PERCEIVED LEADER MINDFULNESS, PERFORMANCE APPRAISAL DISSATIFICATION TERHADAP TURNOVER INTENTION DI MEDIASI OLEH LEADER MEMBER EXCHANGE PADA KARYAWAN BANK MANDIRI KECAMATAN BEKASI SELATAN - Khayla Sekar Larasati; Netania Emilisa; Siti Nurhaliza Sefa Putri Pratama; Nurreva Gesela Neir (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
The aim of this research is to see whether there is an influence of Perceived Leader Mindfulness, Performance Appraisal Dissatisfaction on Turnover Intention mediated by LMX among Bank Mandiri employees, South Bekasi District. This research design was carried out by hypothesis testing. The data used was cross sectional. From the descriptive statistical results of Perceived Leader Mindfulness, it shows that bank employees quite feel the existence of Perceived Leader Mindfulness at Bank Mandiri, South Bekasi District. The results of hypothesis testing show that Perceived Leader Mindfulness has a positive influence on Turnover Intention. The results of hypothesis testing show that Performance Appraisal Dissatisfaction does not have a positive influence on Turnover Intention. The results of hypothesis testing show that LMX has a positive influence on Turnover Intention. The results of hypothesis testing show that Perceived Leader Mindfulness does not have a positive influence on LMX. The results of hypothesis testing show that Performance Appraisal Dissatisfaction has a positive influence on LMX.